Inhibition of hyperactivity of the dorsal raphe 5‐HTergic neurons ameliorates hippocampal seizure. (6th May 2021) - Cheng, Heming; Qi, Yingbei; Lai, Nanxi; Yang, Lin; Xu, Cenglin; Wang, Shuang; Guo, Yi; Chen, Zhong; Wang, Yi
Abstract: Aims: Epilepsy, frequently comorbid with depression, easily develops drug resistance. Here, we investigated how dorsal raphe (DR) and its 5‐HTergic neurons are implicated in epilepsy. Methods: In mouse hippocampal kindling model, using immunochemistry, calcium fiber photometry, and optogenetics, we investigated the causal role of DR 5‐HTergic neurons in seizure of temporal lobe epilepsy (TLE). Further, deep brain stimulation (DBS) of the DR with different frequencies was applied to test its effect on hippocampal seizure and depressive‐like behavior. Results: Number of c‐fos + neurons in the DR and calcium activities of DR 5‐HTergic neurons were both increased during kindling‐induced hippocampal seizures. Optogenetic inhibition, but not activation, of DR 5‐HTergic neurons conspicuously retarded seizure acquisition specially during the late period. For clinical translation, 1‐Hz‐specific, but not 20‐Hz or 100‐Hz, DBS of the DR retarded the acquisition of hippocampal seizure. This therapeutic effect may be mediated by the inhibition of DR 5‐HTergic neurons, as optogenetic activation of DR 5‐HTergic neurons reversed the anti‐seizure effects of 1‐Hz DR DBS. However, DBS treatment had no effect on depressive‐like behavior. Conclusion: Inhibition of hyperactivity of DR 5‐HTergic neuron may present promising anti‐seizure effect and the DR may be a potential DBS target for the therapy of TLE. Abstract : Activity of the DR and its 5‐HTergic neurons remarkably increase during hippocampal kindling seizure. Either optogenetic inhibition of DR 5‐HTergic neurons or 1‐Hz DR DBS significantly retards seizure acquisition. The hyperactivity of the DR may serve as an underlying mechanism for propagation of seizure and the DR may be a potential DBS target for the treatment of epilepsy.